Comparison of high‐intensity focused ultrasound ablation and secondary myomectomy for recurrent symptomatic uterine fibroids following myomectomy: a retrospective study. (3rd May 2020) - Liu, X; Tang, J; Luo, Y; Wang, Y; Song, L; Wang, W
Abstract : Objective: To compare the long‐term symptom alleviation and re‐intervention of high‐intensity focused ultrasound (HIFU) ablation and secondary myomectomy for women with recurrent symptomatic uterine fibroids following myomectomy. Design: A retrospective analysis. Setting: A general hospital in China. Population: One hundred and eighty‐eight women with recurrent symptomatic uterine fibroids following myomectomy. Methods: Women who underwent HIFU ablation ( n  = 101) and secondary myomectomy ( n  = 87) at Chinese PLA General Hospital from January 2008 to December 2016 were analysed. Symptom relief and recurrence were evaluated using the transformed symptom severity scale (tSSS). The additional intervention and treatment‐related complications were also recorded and compared. Main outcome measures: Difference in symptom alleviation, recurrence, re‐intervention and complications. Results: Follow‐up time was comparable for the two groups (56 versus 60 months; P  = 0.88). Regarding tSSS, at 3 months there was improvement in all tSSS for both treatment groups. The time to re‐intervention was shorter in the myomectomy group. The cumulative risk for re‐intervention after HIFU ablation at 1 and 3 years was lower than that after secondary myomectomy (0% versus 4.8%, 3.2% versus 11.9%, respectively); however, no significant difference was observed at 5 and 8 years. There were fewer adverse events in the HIFU ablation group than the myomectomy group (59.4% versus 77%, P  = 0.01). Conclusions: High‐intensity focused ultrasound ablation of recurrent symptomatic uterine fibroids offers comparable long‐term alleviation of symptoms with longer time interval to re‐intervention and fewer adverse events compared with secondary myomectomy. Tweetable abstract: High‐intensity focused ultrasound ablation of recurrent uterine fibroids offered a longer time interval to re‐intervention and fewer adverse events compared with myomectomy. Tweetable abstract: High‐intensity focused ultrasound ablation of recurrent uterine fibroids offered a longer time interval to re‐intervention and fewer adverse events compared with myomectomy.